Smart Parenting in Building Children’s Personality Through Religion-Based Habituation - Fathor Rosi; Fathor Rozi; Hasan Baharun; Elok Fadilatur Rizqiyah (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to analyze and examine the role of religion-based habituation in the development of children's personalities in Besuk Agung village. Problems in the development of children are the subject of this case study, which focuses on a specific object. Observation and in-depth interviews are used to gather the information. Observations and interviews can be strengthened by documenting the results of the research. It is necessary to employ data reduction, presentation, and conclusion techniques when analyzing the data. Findings from the study show that religious habituation can help children develop their communication skills by providing ongoing learning and exposure to educational films, as well as by teaching them about Islam and its stories. It is thus possible to train children to control their emotions, learn to be fair, honest, helpful, and willing to share a high attitude of solidarity and mutual respect through religious-based habituation.